Effects of Surface Coating Preparation and Sliding Modes on Titanium Oxide Coated Titanium Alloy for Aerospace Applications - Bo Yuan Peng; Xueyuan Nie; Ying Chen (International Journal of Aerospace Engineering)
This paper investigates the mechanical response of a coated Ti-6Al-4V alloy surface under different sliding contact stress conditions. The surface was coated with an oxide ceramic material created through the use of a recently developed technique known as plasma electrolytic oxidation (PEO). During the PEO procedure, a composition of silicate and phosphate was used as the electrolyte. In order to evaluate the coating, pin-on-disk (POD) tribology tests and cyclic inclined sliding tests were used under dry room conditions. Furthermore, scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) were utilized to examine the morphology and composition of the coating surfaces. The results of the POD tests revealed that the PEO coating could have a low coefficient of friction and suggested that high silicon concentrations in the PEO coatings take away oxygen from stoichiometric Ti oxides to create lubricating oxides. In addition, cyclic inclined sliding tests showed that smaller pores on the surface of the coating could permit a higher coating cohesive strength and allow the coated Ti alloy surface to perform better under high inclined sliding forces.